Kata Adverba atau Kata Sifat? (Jurnal Bahasa, 2012)
This article aims to clarify the nature of Malay kata sifat (adjectives) that serve as the modifiers of verbs. In English, a word that describes a verbs is an adverb, which is similar in the Malay language. However, in this study some words in the verb modifier slots remain as adjectives and not adverbs. There are four reasons why these are adjectives and not adverbs-there is no change in the morphology; the adjectives maintain the same position, which is that of modifier; there is a difference between the slot and filler elements; lastly, that only words and not word classes can be translated. Based on these four characteristics, it can be concluded that not all adjectives can be treated as adverbs. To describe this, the slot and filler technique is used. Data were collected from five women's biographies (about 150 000 words). These words were uploaded into the Word Smith 4 programme to facilitate the analysis of the behavior of adjectives.Keywords: slot, filler, adjectives, adverbs, syntactic drif